Strategic decision making in the incentives changes early warning and response system - Rogov, Viacheslav; Рогов, В’ячеслав (My University, 2019)
The probability evaluation mechanism of changes in economic incentives and associated risks is developed. It provides an opportunity to manage the corporate development strategy and its current implementation. Expert determination of the amount of loss or lost profit due to the economic incentives changes according to existing or alternative enterprise development strategy with a certain confidence level and decision making about the appropriateness of changing the corporate strategy is suggested. The proposals on formation of methodical approach to economic risks assessment are given. It allows to provide reliable quantitative risk assessment of the corporate development strategy implementation using mathematical apparatus of the generalized fuzzy numbers theory, even when expert groups are formed by specialists with different experience and professional level.
Прийняття стратегічних рішень в системі раннього попередження і реагування на зміни економічних стимулів
Rogov, V. Strategic decision making in the incentives changes early warning and response system = Прийняття стратегічних рішень в системі раннього попередження і реагування на зміни економічних стимулів / V. Rogov // Economic and Law Paradigm of Modern Society. – 2019. – Iss. 2. – P. 21–29.
Keywords: strategic decisions; early warning and response system; incentives; strong signals; weak signals; fuzzy numbers; probability; стратегічні рішення; система раннього попередження і реагування; стимули; сильні сигнали; слабкі сигнали; нечіткі числа; ймовірність